Immunization education for internal medicine residents: A cluster-randomized controlled trial. Issue 14 (27th March 2018) - Whitaker, Jennifer A.; Poland, Caroline M.; Beckman, Thomas J.; Bundrick, John B.; Chaudhry, Rajeev; Grill, Diane E.; Halvorsen, Andrew J.; Huber, Jill M.; Kasten, Mary J.; Mauck, Karen F.; Mehta, Ramila A.; Olson, Timothy; et al.
Abstract: Purpose: The aims of this study are to evaluate the impact of a novel immunization curriculum based on the Preferred Cognitive Styles and Decision Making Model (PCSDM) on internal medicine (IM) resident continuity clinic patient panel immunization rates, as well as resident immunization knowledge, attitudes, and practices (KAP). Methods: A cluster-randomized controlled trial was performed among 143 IM residents at Mayo Clinic to evaluate the PCSDM curriculum plus fact-based immunization curriculum (intervention) compared to fact-based immunization curriculum alone (control) on the outcomes of resident continuity clinic patient panel immunization rates for influenza, pneumococcal, tetanus, pertussis, and zoster vaccines. Pre-study and post-study immunization KAP surveys were administered to IM residents. Results: Ninety-nine residents participated in the study. Eighty-two residents completed pre-study and post-study surveys. Influenza and pertussis immunization rates improved for both intervention and control groups. There was no significant difference in immunization rate improvement between the groups. Influenza immunization rates improved significantly by 33.4% and 32.3% in the intervention and control groups, respectively. The odds of receiving influenza immunization at the end of the study relative to pre-study for the entire study cohort was 4.6 (p < 0.0001). The odds of having received pertussis immunization at the end of the study relative to pre-study for the entire study cohort was 1.2 (p = 0.0002). Both groups had significant improvements in immunization knowledge. The intervention group had significant improvements in multiple domains that assessed confidence in counseling patients on immunizations. Conclusions: Fact-based immunization education was useful in improving IM resident immunization rates for influenza and pertussis. The PCSDM immunization curriculum did not lead to increases in immunization rates compared with the fact-based curriculum, but it did significantly increase resident confidence in communicating with patients about vaccines.